Enhanced Network Security Hybrid Cloud Workflow Scheduling Using Levy-Optimized Slime Mould Algorithm - Guan, Jingang (Informatica, 2025)
Mainstream network security models based on PSO and other algorithms have not been optimized for hybrid cloud environments, resulting in limitations in their application. To ensure network security in hybrid cloud environments, the study first introduces the Levy distribution, uses the Levy distribution to generate random numbers and redesign the position update formula. Then, the penalty parameters of SVM and the radial basis kernel function parameters of SVM are used as individuals to improve SMA. After iteration, the optimal position is the optimal solution of the two parameters. After determining the optimal parameters, an improved slime mould algorithm optimization algorithm is designed. Finally, the algorithm is applied to the encoded hybrid cloud workflow scheduling to propose a method based on the improved slime mould algorithm. The test results showed that when the number of tasks was 1000, the proposed algorithm took 13.7 hours to run, which was better than the traditional 18.2 hours and more than 50 hours of the particle swarm algorithm (P